Henri Bergson's intuitionism as a catalyst of interpreting processes - O. I. Onyschenko, (Ukrainian Cultural Studies, 2020)
The article analyses the process of intuitionism's "entry" into European philosophical – aesthetical and studying of art area from 1913 – the year of publishing the first English speaking interpretation of the French thinker.It is shown as the line of thesis of his philosophical conception transformed into the sphere of artistic creation and influenced on the art of the XX century. The examples of intuitionism's interpretation which are represented in modern Ukrainian human science have been accented. It is underlined that the first experience of English – language interpretation of Henri Bergson's ideas, whose works were very popular in European cultural area, is connected with the name of Gerbert Wildom Karr (1859 – 1931), who proposed popular account of the French theorists views in the work The philosophy of Bergson.The accent is made on the fact that G.W. Karr's interpretational model uses the principle of systematization of "the problem field" which H. Bergson formed during the first decade of the XX century. Special attention is paid to"intuitionalism" – composed part of "bergsonism" in the context of which a special theoretic loading lies on the factors "memory" and "time". Examining "time" H. Bergson proposes to take into consideration its "reversibility" and "non-reversibility".It is shown that factors "memory" and "time" were actively used in avant-garde art and in "logic – alogic" of the building of literary works of the school of "new novel" and in European cinematograph of the 70 – 80 years of the ХХ century. As a good example of aesthetic-artistic embodiment of the modifications of "memory" and "time" the creation of famous Spanish producer Karlos Sauro has been considered. It is emphasized that a special load in the general system of views of H. Bergson is "intuitionism", which in the European cultural space was highly appreciated by both the philosophical community and artists. It is emphasized that such factors of "intuitionism" as intelligence, instinct, intuition, time, memory, are still relevant in the research field.
Keywords: intuitionism, interpretation, intuition, instinct, intellect, time, memory